STUDI DESKRIPTIF KANDUNGAN TIMBAL (Pb) DALAM URINE PADA PEDAGANG ASONGAN DI SEKITAR JUMBO PASAR SWALAYAN KOTA MANADO - Andryes Papuling (POLTEKKES KEMENKES MANADO, 2011)
Danger posed by the use of Lead (Pb) is the most frequent cause poisoning caused by environmental pollutan or air, especially in big cities. The purpose of this study is desktiptive is to provide an overview of the content of Lead (Pb) contained in urine hawkers. The data was collected by direct observation in the field by using a questionnaire that is then followed by laboratory examination. The population of hawkers is around Jumbo Supermarket Manado, sampling as many as 15 samples taken by purposive sampling. Threshold values for the content Lead (Pb) in urine of 150 μg/ml creatinine. The result contain Lead (Pb) in urine hawkers around Jumbo Supermarket Manado still under the Treshold Value is <10 μg/L creatinine, when compared objective criteria of 150 μg/ml creatinine. Can be concluded that the result are still below the specified Treshold Value. Suggest for relevant agencies such as the Environment Agency to condact surveillance on a regular basis with efforts to redunce the amount of air pollution, especially of Lead (Pb).